Modern parenting: An ethical way to nurture children in digital era - Burhan, Oemar Syarif; Praditia, Wahyu Eka; Admodjo, Bhimantoro Suryo; Yuniarto, Gustinar Yus; Ghosh, Anusua (Association for Scientific Computing Electrical and Engineering, 2021)
The internet becoming more sophisticated and advancing at a tremendous rate is also a concern for parents. As children are introduced to the online platform, parents worry about their safety and nurture them from potential risks. Parents gradually develop their parenting methods in this era by learning from community websites, blogs, social media, and apps. The information equips them to deal with their children when playing with electronic devices or surfing websites. There are various types of Parenting Styles, from strict about precluding parenting. When parents are strict, they will be using technology that can monitor or track their children's activities by remotely accessing their children's device, camera, recording text messages, and locations. This type of parenting does make their children feel very uncomfortable. On the other hand, not being concerned about their children accessing the internet can be very dangerous as they can access any sites that are not allowed for their age. This article will review previous Digital Parenting experiences and analyze/design a solution around what parents should do when nurturing and guiding their children for a better future in this digital age.